Efektifitas Pemanfaatan Benda Lokal Sebagai Sumber dan Media Pembelajaran PAI - Habib Ahmadi; Lubna Lubna; Wildan Wildan (Pendekar: Jurnal Pendidikan Berkarakter, 2025)
Abstract: Abstract: This study aims to analyze the effectiveness of utilizing local objects as sources and media for Islamic Religious Education (IRE). The study uses a qualitative method with a library research approach that focuses on reviewing literature from various scientific sources, including journals indexed by Google Scholar and Scopus, as well as relevant books published between 2015 and 2025. Data were collected through systematic analysis of previous studies that examined the implementation of learning media based on the surrounding environment in the context of PAI. The results of the study show that the use of local objects has been proven effective in improving students' understanding of religious concepts, learning motivation, and active involvement. This approach allows students to relate Islamic values to the social and cultural realities in their environment, making learning more contextual, applicable, and meaningful. The scientific contribution of this study lies in its comprehensive synthesis, which affirms the position of local objects not only as visual media or learning aids, but as an epistemic framework that connects the construction of Islamic knowledge with the life experiences of students. This novelty reinforces the theoretical argument that context-based PAI learning is capable of expanding the student-centered learning paradigm towards a humanistic, constructivist, and culturally-rooted pedagogical approach. Practically, these findings have important implications for the development of Islamic education learning design, namely the need for teachers to utilize the environment as a laboratory of values, so that religious learning can function more effectively in shaping the religious and social character of students. Thus, the utilization of surrounding objects becomes a strategic innovation that is not only educationally relevant but also adaptive to the needs of 21st-century learning based on context and real experiences.Abstrak: Penelitian ini bertujuan untuk menganalisis efektivitas pemanfaatan benda lokal sebagai sumber dan media pembelajaran Pendidikan Agama Islam (PAI). Penelitian menggunakan metode kualitatif dengan pendekatan library research yang berfokus pada telaah literatur dari berbagai sumber ilmiah, termasuk jurnal terindeks Google Scholar dan Scopus serta buku-buku relevan yang diterbitkan pada rentang 2015–2025. Data dikumpulkan melalui analisis sistematis terhadap penelitian-penelitian terdahulu yang mengkaji implementasi media pembelajaran berbasis lingkungan sekitar dalam konteks PAI. Hasil kajian menunjukkan bahwa penggunaan benda lokal terbukti efektif dalam meningkatkan pemahaman konsep keagamaan, motivasi belajar, dan keterlibatan aktif peserta didik. Pendekatan ini memungkinkan siswa mengaitkan nilai-nilai Islam dengan realitas sosial dan budaya di lingkungan mereka, sehingga pembelajaran menjadi lebih kontekstual, aplikatif, dan bermakna. Kontribusi ilmiah penelitian ini terletak pada sintesis komprehensif yang menegaskan posisi benda lokal tidak hanya sebagai media visual atau pendukung pembelajaran, tetapi sebagai kerangka epistemik yang menghubungkan konstruksi pengetahuan Islam dengan pengalaman hidup peserta didik. Novelty ini memperkuat argumentasi teoritis bahwa pembelajaran PAI berbasis konteks lokal mampu memperluas paradigma student-centered learning menuju pendekatan pedagogis yang humanis, konstruktivistik, dan berakar pada budaya. Secara praktis, temuan ini memberikan implikasi penting bagi pengembangan desain pembelajaran PAI, yakni perlunya guru memanfaatkan lingkungan sebagai laboratorium nilai, sehingga pembelajaran agama dapat berfungsi lebih efektif dalam membentuk karakter religius dan sosial peserta didik. Dengan demikian, pemanfaatan benda sekitar menjadi inovasi strategis yang tidak hanya relevan secara edukatif, tetapi juga adaptif terhadap kebutuhan pembelajaran abad 21 yang berbasis konteks dan pengalaman nyata.